Chatzigrigoriou, Pavlos - (:unkn) unknown (My University, 2026)
I am a Civil Engineer, since 1998. I have been self employed for four (4) years. During that period I finished my first MSc in Architecture. Also, I worked on the field of Restoration (Buildings, Monuments, even Cities). At that period, I worked for the restoration of buildings that were damaged from the 1999 Athens Earthquake. I was a construction site junior manager and an office engineer for studies on damaged buildings. At 2002 I started working in Municipality of Syros, a Greek Island in Cyclades. I was an Urban Planning Engineer and I studied the pathology of the 19th century buildings in the island, participating in many restoration projects of historical buildings. From 2005 to now, while working in Syros, I finished a second MSc in Environmental Building Planning and a PhD in Building Pathology. I am using new technology in my studies and in my work. I use G.I.S. and Databases for reporting and supervising historical buildings. I like teaching, studying and reading in my field. Specialties: Engineering, Architecture, Urban Planning, Environmental Protection, CAD user, GIS user, ability to teach, fast learner.